MANAJEMEN PENDIDIKAN KARAKTER PADA SEKOLAH DASAR MUHAMMDIYAH 10 BANJARMASIN - Achmad Fauzi (Pahlawan, 2020)
Management Character Education in Elementary Schools Muhammadiyah 10 Banjarmasin. The problem in this study were : (1) how were character education planning and organizing in SD Muhammadiyah 10 Banjarmasin? , (2) how the implementation of character education was implemented in Muhammadiyah 10 Banjarmasin?, and (3) how to control the character education in Muhammadiyah 10 Banjarmasin?. The purpose of this study was : (1) to determine the character of educational planning in SDMuhammadiyah 10 Banjarmasin (2) to determine the organization of the implementation of character education in SD Muhammadiyah 10 Banjarmasin, (3) to assess the implementation of character education in Muhammadiyah 10 Banjarmasin, and (4) to determine the character of educational supervision of SD Muhammadiyah 10 Banjarmasin.The research object in this study were all residents of State Muhammadiyah 10 Banjarmasin, which consists of the Principal, the Vice Principal, teachers of religion, parents, and students of SD Muhammadiyah 10 Banjarmasin. This research approach using qualitative research , data collection procedures used were : (1) observation , (2) interviews , and (3) documentation and data analysis techniques in the form of qualitative techniques as well as checking the validity of the data is done by making observations and re -check that the data collected can be accounted. The results obtained are: (1) planning of character education in Muhammadiyah 10 Banjarmasin involving all teachers , (2) the organization of character education in Muhammadiyah 10 Banjarmasin involving the entire school (3) the implementation of character education in Muhammadiyah 10 Banjarmasin. wellestablished as communication in the mix works well and (4) supervision of character education in SDM 10 Banjarmasin work together all components.